Investigation of the parasite load in birds destined for human consumption, at a fair in the City of Porto Velho-RO, Brazil (Research, Society and Development, 2021)
This study aimed to establish the prevalence of parasitosis in domesticated hens, reared in extensive regime in the city of Porto Velho, Rondônia, Brazil. Forty bird fecal samples were analyzed in 4 (four) farms, 10 in each of them. The samples were then processed by the qualitative technique of Willis & Mollay (simple flotation, 1921). Of the 40 stool samples analyzed, 32 were positive and 8 negative, and of these 32, 9 had mixed infections. The eggs of the parasites that were found in the exams are the following: Heterakis sp, Capillaria sp, Prorrocaecum sp, Eimeria sp, Trichomonas sp, Serratospiculum sp, Isospora sp, and Microtetraneres sp. The parasitological analysis performed on fecal samples proved to be an adequate device to help control worms. Despite the prevalence of parasites that were detected in high quantities, the breeders did not show or report health problems in the birds. The work concluded that there is a high parasite load in the chickens sold by this property, leading to a serious risk for human consumers of these birds, such as possible food poisoning.